Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ppl.12904
|View full text |Cite
|
Sign up to set email alerts
|

Illumina‐based transcriptomic analysis on recalcitrant seeds of Panax notoginseng for the dormancy release during the after‐ripening process

Abstract: Panax notoginseng (Burk) F.H. Chen is an economically and medicinally important plant of the family Araliacease, with seed dormancy being a key factor limiting the extended cultivation of P. notoginseng. The seeds belong to the morphophysiological dormancy (MPD) group, and it has also been described as the recalcitrant seed. To date, the molecular mechanism of dormancy release in the recalcitrant seed of P. notoginseng is unknown. In the present study, the transcript profiles of seeds from different after-ripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In addition to ABA and GA, which are two major hormones that respectively induce and break seed dormancy in most plants, other phytohormones, such as cytokinins, jasmonic acid, strigolactones, brassinosteroids, ethylene, salicylic acid, and auxin, may also regulate seed dormancy and germination in a plant species-dependent manner. Their contents in dormant and germinating seeds are partly regulated by the expression of genes related to hormone metabolism and signaling [ 40 , 46 ]. In this study, we identified 475 putative hormone metabolism-related unigenes and 510 putative hormone signaling genes that were differentially expressed during P. sibiricum seed dormancy and seedling and shoot emergence (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ABA and GA, which are two major hormones that respectively induce and break seed dormancy in most plants, other phytohormones, such as cytokinins, jasmonic acid, strigolactones, brassinosteroids, ethylene, salicylic acid, and auxin, may also regulate seed dormancy and germination in a plant species-dependent manner. Their contents in dormant and germinating seeds are partly regulated by the expression of genes related to hormone metabolism and signaling [ 40 , 46 ]. In this study, we identified 475 putative hormone metabolism-related unigenes and 510 putative hormone signaling genes that were differentially expressed during P. sibiricum seed dormancy and seedling and shoot emergence (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…ABI3 and ABI5 are two ABA signaling-related genes that positively control seed dormancy [ 43 ]. ABI5 is found highly expressed in dormant seeds of several plant species [ 19 , 46 ]. Their homologous genes in P. sibiricum were expressed at higher levels in the Seed and Corm stages than in the cold-stratified germinated seeds and seedlings, implying ABA may have accumulated during the Seed and Corm stages under warm conditions, leading to the dormancy of the Seed and Corm stages.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis on Panax notoginseng (Burk) F.H. Chen seeds revealed 78 differentially expressed genes associated with seed dormancy; of these, 15 genes were involved in the abscisic acid and GA 3 pathways [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, enrichment pathway analysis revealed pathways potentially associated with seed dormancy releases, such as steroid biosynthesis, avonoid biosynthesis, avone and avonol biosynthesis, and starch and sucrose metabolism [29], and a transcriptomic analysis on Panax notoginseng (Burk) F.H. Chen seeds revealed 78 differentially expressed genes (DEGs) associated with seed dormancy, and among them, 15 DEGs were involved in abscisic acid (ABA) and GA 3 pathways [35].…”
Section: Discussionmentioning
confidence: 99%